Antibiotic use in different hospital administrative categories: an overview of 10 years of a statewide surveillance program in Brazil - Filipe Piastrelli; Denise Brandão de Assis; Geraldine Madalosso; Ícaro Boszczowski (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract